Does laparoscopic appendectomy confer advantages over open appendectomy for pediatric complicated appendicitis? A single institute experience - Murali, Govindappa Saroja; Misra, Richa; Parashar, Gaurav; Santhanakrishnan, Ramesh (Indian Journal of Child Health, 2020)
Introduction: Laparoscopic appendectomy (LA) for complicated appendicitis appears to be controversial due to the difficulty in dissection and clearing off the peritoneal contamination, prolonged operating times, higher incidence of post-operative abdominal abscess, and wound infections. Objectives: The objective of the study was to compare laparoscopic and open appendectomy (OA) and evaluate the outcome of LA in children with complicated appendicitis. Materials and Methods: A retrospective analysis of 182 patients’ records with complicated appendicitis was done. Data collected included demographics, operative time, resumption of oral intake, and infectious complications such as wound infection and intra-abdominal abscess, need for redo surgery, length of hospitalization, and duration of antibiotic use. Patients were followed up for 6 months in the post-operative period to assess delayed complications. Results: LA was performed in 102 patients and 80 patients underwent an OA. The two groups did not differ significantly in mean age, duration of antibiotic use, resumption of oral intake, and length of the hospital stay. The duration of surgery was significantly longer for LA (p<0.0001). However, the wound infection was significantly more common in the OA group than the laparoscopy group (p=0.0058). None of the patients in the LA group developed delayed complications. A total of four patients in the open group had to undergo surgery for late-onset complications. Conclusion: LA for complicated appendicitis is more advantageous than OA as there is reduced surgical site infection. However, the operative time is prolonged with an increased incidence of immediate post-operative intestinal obstruction. Nevertheless, it avoids the late complications of OA.